A Regional Computable General Equilibrium Analysis of Property Tax Rate Caps and a Sales Tax Rate Increase in Indiana - Nalitra Thaiprasert (2018)
We use a regional computable general equilibrium (CGE) model and Indiana data to examine both the short-run and the long-run effects of property tax rate limits and an increase in the sales tax rate. We find that the property tax caps and sales tax rate increase have a relatively small impact on aggregate economic measures in the short run and a positive effect in the long run. Higher-income households experience larger increases in income than lower-income households in terms of the dollar amount of the increase, but lower-income households experience larger gains as a percentage of labor income. The value of output (sales) increases in the long run with construction, certain manufacturing industries, and wholesale trade experiencing the largest increases. © The Author(s) 2013.